2019
DOI: 10.1111/disa.12372
|View full text |Cite
|
Sign up to set email alerts
|

Flooding and the ‘new normal’: what is the role of gender in experiences of post‐disaster ontological security?

Abstract: Disaster researchers have long analysed disruption to affected residents' ontological security, often represented by routines and familiar landmarks. Surprisingly little of this work, though, assesses who is most likely to experience feelings of disruption. Using a representative set of survey data, complemented by follow‐up interview data from 40 residents affected by the Southern Alberta Flood of June 2013, this paper explores how demographic characteristics, such as gender and place attachment, impact on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…Yet what it means to stay in place in the context of climate change is as varied, uncertain, and shifting as are the experiences and outcomes associated with planned relocation, warranting fresh attention from scholars. Studies underscore the psychological toll that a radically altered post-disaster landscape can take on residents who return or remain, particularly those who have lived in the location for a long time and possess stronger place attachment and local social ties (Haney and Gray-Scholz 2020). Meanwhile, terms such as "solastalgia" and "stationary displacement" or "displacement in place" speak to the psychically-and often physically-damaging consequences of witnessing one's home and the surrounding environment degraded in ways that may be gradual but no less violent than sudden disruption (Albrecht et al 2007;Nixon 2011).…”
Section: Assessing Outcomes Of Retreat Versus Rebuildingmentioning
confidence: 99%
“…Yet what it means to stay in place in the context of climate change is as varied, uncertain, and shifting as are the experiences and outcomes associated with planned relocation, warranting fresh attention from scholars. Studies underscore the psychological toll that a radically altered post-disaster landscape can take on residents who return or remain, particularly those who have lived in the location for a long time and possess stronger place attachment and local social ties (Haney and Gray-Scholz 2020). Meanwhile, terms such as "solastalgia" and "stationary displacement" or "displacement in place" speak to the psychically-and often physically-damaging consequences of witnessing one's home and the surrounding environment degraded in ways that may be gradual but no less violent than sudden disruption (Albrecht et al 2007;Nixon 2011).…”
Section: Assessing Outcomes Of Retreat Versus Rebuildingmentioning
confidence: 99%
“…Following Hurricane Katrina, Hawkins and Maurer (2011) demonstrated how residents of New Orleans’ Lower 9th Ward experienced these feelings of disruption and sought a return to normal. Along similar lines, Haney and Gray-Scholz (2020) found that many flood-affected residents reported a disruption to their familiar routines and landmarks and, importantly, that this disruption was much more common for women than for men. Other research also demonstrates the profound disruption of residents’ ontological security after disaster (Akerkar and Fordham 2017; Gorman-Murray, McKinnon, and Dominey-Howes 2014; Reid and Beilin 2015; Sousa, Kemp, and El-Zuhairi 2014; Zaretsky 2002).…”
Section: Review Of Literature and Theorymentioning
confidence: 71%
“…Although many interviewees discussed their demographics, we did not ask demographic questions specifically. This is because we conducted a survey of the 26 floodaffected neighborhoods only one year earlier (see Gray-Scholz et al 2019;Haney 2018;Haney and Gray-Scholz 2020;Milnes and Haney 2017). That survey indicated that the neighborhoods were affluent (median income $100,000-$109,999), white (over 90%), educated (63% holding a Bachelor's degree or higher), and homeowners (over 75%).…”
Section: Methodsmentioning
confidence: 99%